Open Source Data and Strategic Project for Resilient City - Cristina Càndito; Manuel Gausa; Matilde Pitanti; Giulia Sola (Agathón)
This contribution explores the role of information technology, relating to the representation and processing of data in open source and crowd-sourced format, for the purpose of urban planning and design process. In the research field, an experimental analysis is carried out within the Genoese neighborhood of Molassana by comparing and processing, in a single system, the traditional cartography provided by the online portals of the public administration and the data shared by users on social networks and open source platforms. The complexity of the information obtained grows a synthetic multi-layer territorial strategy, strongly linked to the local and social context.